PERANCANGAN MESIN PENGOLAH LIMBAH LIDI KELAPA SAWIT MENGGUNAKAN COMPUTER AIDED DESIGN (CAD) - Arsi, Fadli; Nando , Fiky Two (Jurnal Teknik Industri Terintegrasi (JUTIN), 2021)
Abstract Riau is one of the areas with the largest oil palm plantation area in Indonesia. In general, oil palm has three types of waste, including: solid waste, liquid waste, and gas waste. Solid waste consists of empty bunches, midribs, stems and mesocarp fibers. The frond waste is generated when trimming the midrib at the time of harvesting oil palm fruit bunches. The oil palm midrib consists of rachis (leaves), pinnacs (leaves), and spines (sticks). The number of leaflets on one midrib ranges from 250-400 leaflets located on the left and right of the midrib. Each leaflet consists of a stick and two leaves. The process of separating sticks is still done manually, so it takes a long time to separate them. So in this study, we designed a palm stick machine using CAD. Designing with CAD provides many advantages including making it easier for designers to design, reducing time, and reducing costs during design. There are three design pictures of palm oil stick waste processing machines. Based on economic calculations, tools and materials needed and processing time, design drawing C is the choice. Next, build a waste treatment machine with reference to the selected design Keywords: stick waste, CAD, Palm Oil